The Community Engagement in Mental Health Advocacy: An Inter-University Program in Malaysia - Ratna Yunita Setiyani Subardjo; Zeeshan Khan (Journal of Social and Community Development, 2025)
This study explores the role of community engagement in mental health advocacy, focusing on academically driven initiatives conducted by Ratna Yunita Setiyani Subardjo in Malaysia. Utilizing a qualitative descriptive method, the research draws on institutional reports and participatory observations, framed by community psychology and participatory action research (PAR). Key activities included mental health campaigns, psychological counseling, educational outreach, and capacity building, all implemented in collaboration with institutions such as Universiti Kebangsaan Malaysia and Universitas Aisyiyah Yogyakarta. The interventions addressed student mental health through culturally sensitive, bilingual services and peer support models. Findings indicate that academic institutions can serve as powerful agents of social transformation when their members actively engage in community well-being. These initiatives significantly contributed to emotional resilience, stigma reduction, and inclusive mental health literacy. This case highlights the potential of cross-cultural academic partnerships in promoting sustainable and human-centered mental health practices.